Reporting 3 cases of progressive systemic sclerosis with internal tooth resorption - M. Saheb Jami; M. Eslami Amirabadi (Tehran University of Medical Sciences, 1992)
The following reports are introducing 3 patients with progressive systemic sclerosis who had oral manifestations such as limited mouth opening, PDL thickening,... as well as uncommon internal resorption in many of their teeth with any etiologic factor. According to oral manifestations of systemic sclerosis, It seems that internal resorption can be associated to their systemic disease.